2016
DOI: 10.3762/bjoc.12.103
|View full text |Cite
|
Sign up to set email alerts
|

Efficient syntheses of climate relevant isoprene nitrates and (1R,5S)-(−)-myrtenol nitrate

Abstract: SummaryHere we report the chemoselective synthesis of several important, climate relevant isoprene nitrates using silver nitrate to mediate a ’halide for nitrate’ substitution. Employing readily available starting materials, reagents and Horner–Wadsworth–Emmons chemistry the synthesis of easily separable, synthetically versatile ‘key building blocks’ (E)- and (Z)-3-methyl-4-chlorobut-2-en-1-ol as well as (E)- and (Z)-1-((2-methyl-4-bromobut-2-enyloxy)methyl)-4-methoxybenzene has been achieved using cheap, ’off… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
8
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 56 publications
2
8
0
Order By: Relevance
“…The NMR spectra obtained for our synthesised E-(1,4)-IN, Z-(1,4)-IN and (4,3)-IN are identical to those obtained by Lee et al (2014). As reported in Bew et al (2016), Z-(1,4)-IN isomerises rapidly to E-(1,4)-IN, resulting in a mixture of the two isomers, a situation also reported by Lee et al (2014) who found that samples of Z-(1,4)-IN contained approximately 15 % of the E-(1,4)-IN. Similarly, Lockwood et al report similar behaviour for two of their isomers which are clearly separated by HPLC yet are mixtures when analysed by GC.…”
Section: Comparison With Earlier Worksupporting
confidence: 81%
See 2 more Smart Citations
“…The NMR spectra obtained for our synthesised E-(1,4)-IN, Z-(1,4)-IN and (4,3)-IN are identical to those obtained by Lee et al (2014). As reported in Bew et al (2016), Z-(1,4)-IN isomerises rapidly to E-(1,4)-IN, resulting in a mixture of the two isomers, a situation also reported by Lee et al (2014) who found that samples of Z-(1,4)-IN contained approximately 15 % of the E-(1,4)-IN. Similarly, Lockwood et al report similar behaviour for two of their isomers which are clearly separated by HPLC yet are mixtures when analysed by GC.…”
Section: Comparison With Earlier Worksupporting
confidence: 81%
“…Until the very recently reported synthesis of Z-(1,4)-al-IN (Xiong et al, 2016) and our reported synthesis of five of the hydroxy isoprene nitrates by unambiguous means in Bew et al (2016), the only published syntheses of isoprene nitrates were those of three IN isomers separated from mixtures reported in detail by Lockwood et al (2010) and Lee et al (2014). Both groups used the same starting material but differ in the particular but similar nitration conditions employed, and it is quite probable that they synthesised the same isomers, although they identify them differently.…”
Section: Comparison With Earlier Workmentioning
confidence: 78%
See 1 more Smart Citation
“…As reported in Bew et al (2016), the attempted synthesis of (2,1)-IN failed to produce a purified nitrate despite the synthesis of a promising precursor. This was due to the surprisingly low reactivity of the precursor to nitration, despite a number of methods being applied, and the difficulties in separating the reaction products after nitration.…”
Section: Synthesismentioning
confidence: 92%
“…In contrast, our general synthetic approach was to build the isoprene nitrates in stages, which allowed us to design and assemble known carbon skeletons and use protecting group strategies as well as late-stage nitration under mild conditions to ensure selectivity in the location and extent of nitration, thus yield individual, unambiguous isoprene nitrate isomers. We report the synthesis and purification of (4,3)-IN, Z-(1,4)-IN, E-(1,4)-IN, Z-(4,1)-IN, E-(4,1)-IN and acetone nitrate (NOA) in detail in Bew et al (2016; the NMR data are also included in the Supplement of this current paper) while the attempted syntheses of (2,1)-IN, Z-(1,4)-al-IN, E-(1,4)-al-IN and Z-(4,1)-al-IN are described here.…”
Section: Synthesismentioning
confidence: 99%